Racial Microaggressions in the Workplace: A Critical Race Analysis of the Experiences of African American Educators. (April 2016) - DeCuir-Gunby, Jessica T.; Gunby, Norris W.
The purpose of this study was to examine the impact of racial microaggressions, racial/ethnic identity, and coping, as they relate to job satisfaction. We found that the experiencing of racial microaggressions negatively affects job satisfaction and that educators in higher education contexts often engage in detachment coping. Job satisfaction was also affected by marital status and gender. This study is important because it helps to better understand how African American educators cope with the experiencing of racial microaggressions and how this affects their experiences in and perceptions of the workplace.